REACH: Better Knowledge and Better Use of Chemicals in the European Union - Cristina de Avila; Eva C. Sandberg (CHIMIA, 2006)
REACH is the proposed new chemicals regulation in the European Union. It builds on existing legislation, parts of which have been operating for 40 years, while tackling the identified shortcomings of the current system. The main objective of REACH is to improve the knowledge on chemicals, their properties and uses. In order to achieve this objective it is essential that industry assumes its responsibility to hold the knowledge on the substances they are manufacturing or importing and to share this knowledge with the authorities and their downstream users. REACH will require all substances manufactured and imported at and above one tonne per year to be registered. Through the Registration procedure, the obligation of industry to hold and share with authorities their knowledge of chemicals will materialise. REACH aims also to control better the use of substances of very high concern, this obviously includes the restriction of certain substances or certain uses. Through the Authorisation procedure, REACH will allow controlled use of substances of very high concern, such as carcinogens, mutagens and reprotoxic substances, substances that are persistent, bioaccumulative and toxic, and substances that are very persistent and very bioaccumulative. Increased knowledge and increased control, supplemented by substitution of dangerous substances and the fostering of innovation, will have as clear results a higher level of protection of human health and the environment, but additionally will bring along the opportunity to rebuild confidence in chemicals.